Perancangan Perabot Multifungsi Pada Zybrick Coffee Di Surabaya - Michael Dendy (Intra, 2017)
The needs of current café users are still not facilitated well, this makes the existence of this furniture set design in the future add to the productivity and answer the user’s needs in café’s. To make fullest use of this furniture set design in a café in Surabaya, Zybrick Coffee is chosen as the design location, because the consumers here not only enjoy a cup of coffee, but also do other activities (finish some work, gathering, play, etc.) which is why this furniture set design is mostly needed here to accommodate user’s activity.The method used is design thinking, by referring to literature study and field study or Observing the location, then concluding the obtained data, start sketching the alternatives, then sort and select the alternatives to find one design that can best accommodate users flexibly in accordance with the functions and needs.